Science and development of muscle hypertrophy - Schoenfeld, Brad 1962- (Champaign, IL Human Kinetics, 2021)
"Science and Development of Muscle Hypertrophy, Second Edition, is a compilation of science-based principles to help professionals develop muscle hypertrophy in athletes and clients. It highlights the aspects of muscle hypertrophy that are currently being examined, and it tells readers how to apply the research conclusions for maximal hypertrophic development"--Provided by publisher.
Hypertrophy-Related Responses and Adaptations to Exercise Stress -- Mechanisms of Hypertrophy -- Measurement of Muscle Hypertrophy -- Role of Resistance Training Variables in Hypertrophy -- Advanced Training Practices -- Role of Aerobic Training in Hypertrophy -- Factors in Maximal Hypertrophic Development -- Program Design for Maximal Hypertrophy -- Nutrition for Hypertrophy.
Includes bibliographical references and index.
Keywords: Exercise; Physical fitness; Muscles -- Hypertrophy